2008
DOI: 10.1172/jci32830
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone enhances thymic function in HIV-1–infected adults

Abstract: Growth hormone (GH) is an underappreciated but important regulator of T cell development that can reverse age-related declines in thymopoiesis in rodents. Here, we report findings of a prospective randomized study examining the effects of GH on the immune system of HIV-1-infected adults. GH treatment was associated with increased thymic mass. In addition, GH treatment enhanced thymic output, as measured by both the frequency of T cell receptor rearrangement excision circles in circulating T cells and the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(154 citation statements)
references
References 62 publications
8
140
2
4
Order By: Relevance
“…Therefore, an effect on pre-T cell number has to be considered, in addition to the potential direct action on thymus function. Long-term GH treatment of immunodeficient HIV-infected patients leads to increase in thymic mass, in frequency of circulating TREC within PBMC, and in the number of CD4 + T cells [15]. These findings are consistent with animal studies showing that GH is able to stimulate thymopoiesis.…”
Section: Effects On Thymocyte Numbersupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, an effect on pre-T cell number has to be considered, in addition to the potential direct action on thymus function. Long-term GH treatment of immunodeficient HIV-infected patients leads to increase in thymic mass, in frequency of circulating TREC within PBMC, and in the number of CD4 + T cells [15]. These findings are consistent with animal studies showing that GH is able to stimulate thymopoiesis.…”
Section: Effects On Thymocyte Numbersupporting
confidence: 86%
“…These findings are consistent with animal studies showing that GH is able to stimulate thymopoiesis. Furthermore, these increases of TREC frequency and T-cell gain are correlated to an increase of plasma IGF-1 [15], arguing for a crucial role of IGF-1 in GH-mediated stimulation of thymic T-cell production. Investigation of thymopoiesis in adult GH deficiency (AGHD) has demonstrated that, after GH withdrawal, intrathymic T-cell proliferation and thymic T-cell output decreased whereas resumption of GH treatment led to an increase of thymopoiesis to a level close to the one before withdrawal of GH treatment [16].…”
Section: Effects On Thymocyte Numbermentioning
confidence: 94%
See 2 more Smart Citations
“…Previous effort has focused on rejuvenating the thymus (15). Though this approach will be valuable under extreme forms of lymphocyte depletion, such as after chemotherapy or HIV infection (47), it may have little effect on age-associated contraction in diversity. Instead, our model suggests that treatment would require an intervention that targets the specific cells growing abnormally and pushing other TCR lineages toward stochastic extinction.…”
Section: Discussionmentioning
confidence: 99%